2022
DOI: 10.13080/z-a.2022.109.042
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of Sosnowsky’s hogweed (Heracleum sosnowskyi Manden.) in Ukraine

Abstract: Sosnowsky's hogweed (Heracleum sosnowskyi Manden.) is known as an invasive, ineligible, harmful to human health, and hardly controlled plant. The purpose of this study was to evaluate the efficiency of chemical control when different herbicides were applied at various development stages of H. sosnowskyi plants. The experiment was carried out in Ukraine over the period of 2013-2020. Two field experiments on the first-year and second-year H. sosnowskyi plants were conducted. All the selected herbicides were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Desk studies conducted in Germany, the United Kingdom, France, and Sweden on the potential effects of a glyphosate ban on agricultural productivity and farm income concluded that, in particular, no-tillage farming/conservation agriculture will face severe problems without glyphosate to control weeds and cover crops [ 20 ]. Moreover, glyphosate is an important tool, controlling an invasive plant species [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Desk studies conducted in Germany, the United Kingdom, France, and Sweden on the potential effects of a glyphosate ban on agricultural productivity and farm income concluded that, in particular, no-tillage farming/conservation agriculture will face severe problems without glyphosate to control weeds and cover crops [ 20 ]. Moreover, glyphosate is an important tool, controlling an invasive plant species [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%